(untitled) (SAARC Journal of Agriculture, 2023)
Five different locations namely; PSTU campus, BRRI Barishal, RARS Barishal, Dhaka University campus and Mohera Jamidarbari landscapes of Tangail district were selected to study the host range, incidence and damage of the pink hibiscus mealybug. Results revealed that the Pink hibiscus mealybug was found to feed on 22 known host plants from 7 families and 6 unknown host plants. The highest incidence of mealybug per leaf was recorded on century plant and the lowest was on Mussaenda. The highest number of mealybugs per twig was found on Elite patabahar (30) followed by Hibiscus (24) while the lowest number was found on Croton (5). Among five locations the highest percentage of plant infestation was observed at PSTU campus (52%) and the lowest percentage was at BRRI Barishal (35%). The highest percentage of infested leaves per plant was found on Century plant (47%) and the lowest percentage was on Laurentti (12%). The highest percentage of infested twigs per plant was found on Hibiscus (60%) followed by Jatropha (50%) while the lowest percentage was on Maity patabahar (13%). These findings could be helpful to adopt management strategy against Pink hibiscus mealybug in proper time to protect landscape ornamentals and increase beautification. SAARC J. Agric., 21(1): 203-215 (2023)